(untitled) (BIRDEM Medical Journal, 2020)
Background: Lipid abnormalities are more common in type 2 diabetes mellitus and are aggravated with poor glycaemic control. Lipid abnormalities play an important role in atherosclerosis, a leading cause of mortality in patients with diabetes mellitus. Thus there is a need to evaluate lipid profile and glycemic status in type 2 diabetes mellitus population and determine the major lipid risk factors for coronary artery disease. Present study focuses on the dyslipidemic pattern and glycemic status of male and female with type 2 diabetes mellitus. Methods: Total 270 patients with type 2 diabetes,age 30-60 years, both genderwere included for this crosssectional study which was carried out from January 2019 to December 2019at Bogura Diabetic Hospital, Bogura. A Structured questionnaire was prepared for each study subject after taking informed written consent. Detail personal, medical, family and socioeconomic history of study subjects were collected through history taking and review of clinical and biochemical records from the participants. Diabetic patients were diagnosed depending on history, clinical features and American Diabetes Association(ADA) criteria (2018). Fasting blood glucose, glycatedhaemoglobin (HbA1c)), fasting lipid profile were estimated in all study subjects by standard laboratory methods. Appropriate statistical tests were done. Results: Type 2 male diabetes mellitus participants showed mean fasting blood glucose, HbA1c, total cholesterol, triglyceride and low density lipoprotein cholesterol and high density lipoprotein cholesterol were 8.64 ± 3.38(mmol/L),7.86 ± 2.36(%), 233.09 ± 73.71, 198.19 ± 61.38, 152.98 ± 57.33 and 40.41 ± 5.44 (mg/ dl)respectively. Incase of female patients,fasting blood glucose, HbA1c, total cholesterol, triglyceride and low density lipoprotein cholesterol and high density lipoprotein cholesterol 8.59 ± 3.62(mmol/L),7.88 ± 2.496(%),215.899 ± 83.01, 186.18 ± 67.595, 139.10 ± 65.59 and 40.28 ± 5.66 mg/dlrespectively. There were statistically significant difference (p <0.05) of fasting blood glucose, fasting blood glucose, total cholesterol, triglyceride and low density lipoprotein cholesterol between male and female type 2 diabetic patients. Conclusion: Our study had shown that total cholesterol, triglycerides, and low-density lipoprotein levels were significantly increased in male type 2 diabetes mellitus patients, compared with female type 2 diabetes mellitus patients, while high-density lipoprotein had shown a statistically non-significant difference.This study demonstrated the existence of dyslipidemia in male diabetic population than female which is major risk factor for atherosclerosis and coronary artery disease. Birdem Med J 2021; 11(1): 17-21